Quantitation of Phosphotyrosine Signals in Human Prostate Cell Adhesion Sites - Anne E. Cress (BioTechniques)
A simple method is described for the quantitation of phosphotyrosine signaling in human prostate cell cultures. The phosphotyrosine signals are observed by standard immunohistochemistry techniques, and the resulting digital images are analyzed using the Scion image software program. The signals within the cell adhesion sites are quantitated using the density slice and particle analysis features of the software. The immunohistochemistry results are compared with detection of phosphotyrosine signals using a standard Western blotting procedure with whole cell lysates. The resulting data is converted into graphs using the Sigma Plot Program. This method is illustrated using damage-induced signaling within cell adhesion sites after a low dose of ionizing radiation.